The moral panic about the socializing of young people in Minangkabau - Parker, Lyn (UI Scholars Hub, 2014)
This paper analyses the discourse surrounding the perceived threat of free seks and pergaulan bebas (free socializing) to the moral health of young Minangkabau people, and in particular, young women, in West Sumatra. It uses the sociological frame of